2010
DOI: 10.1111/j.1471-4159.2010.06763.x
|View full text |Cite
|
Sign up to set email alerts
|

Excitotoxicity of TNFα derived from KA activated microglia on hippocampal neurons in vitro and in vivo

Abstract: J. Neurochem. (2010) 114, 386–396. Abstract Highly activated microglia and followed excessive expression of inflammatory cytokines are associated with neuroexcitotoxic injuries. We use electrophysiological techniques, ELISA, western‐blot, RT‐PCR assay and TUNEL method to explore whether over‐produced tumor necrosis factor alpha (TNFα) released from activated microglia results in neuronal injuries, and further causes apoptosis through increasing excitotoxicity of hippocampal neurons. Our data showed that kainic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 43 publications
2
39
0
Order By: Relevance
“…Mouse Primary Microglial Culture-Mice at postnatal days 1 to ϳ3 were used to prepare mixed glial cultures according to a previously published protocol (45). Briefly, mixed glial cells were plated onto polylysine-coated culture flasks in DMEM containing 10% fetal bovine serum (FBS), and medium was changed the next day to a medium containing 25 ng/ml of GM-CSF and 10% FBS.…”
Section: Methodsmentioning
confidence: 99%
“…Mouse Primary Microglial Culture-Mice at postnatal days 1 to ϳ3 were used to prepare mixed glial cultures according to a previously published protocol (45). Briefly, mixed glial cells were plated onto polylysine-coated culture flasks in DMEM containing 10% fetal bovine serum (FBS), and medium was changed the next day to a medium containing 25 ng/ml of GM-CSF and 10% FBS.…”
Section: Methodsmentioning
confidence: 99%
“…A cell intrinsic mechanism is indicated by studies that show that KA's neurotoxic effect is receptor-mediated (Ogita et al, 2003(Ogita et al, , 2005Lopez-Picon et al, 2006). Evidence for an extrinsic effect comes from the involvement of glia, particularly microglia, in the death of pyramidal neurons following KA (Hong et al, 2010;Zhu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The prevailing evidence for the role of microglia following kainic acid treatment of the hippocampus is that these glia cells aid the neurodegenerative process (Cho et al, 2008;Hong et al, 2010). Whether this effect is mediated through tissue plasminogen activator or tumor necrosis factor ␣ or another molecule, the end result is the involvement of microglia in enhanced hippocampal neuronal death Zhu et al, 2010). On the other hand, astrocytes have been found to have a protective effect, presumably by dampening the excitotoxicity of glutamate from the local environment (Liang et al, 2008).…”
mentioning
confidence: 99%
“…The long-term presence of immune cells in the brain indicate that BI leads to persistent neuroinflammatory changes and to upregulation of several proinflammatory cytokines such as TNFα, IL-1 IL-6 and their receptors [26,35,36]. Importantly, it was also reported that the inflammatory responses to BI via the production of these cytokines have a neurotoxic effect on hippocampal neurons manifesting by inhibition of neurogenesis and enhanced apoptosis [36,37,38]. These mechanisms may be involved in hippocampal atrophy and neuronal loss as demonstrated in the present study.…”
Section: Discussionmentioning
confidence: 99%